Breath-holding index – a new approach to an old method - Marta Nowakowska-Kotas; Weronika Lisiak; Emilia Wiśniewska; Sławomir Budrewicz; Piotr Wiśniewski (European Journal of Translational and Clinical Medicine, 2025)
Background: Despite technical challenges and uncertainties, transcranial Doppler (TCD) ultrasonography remains a promising tool due to its non-invasive nature, safety, and cost-effectiveness. In this study we aimed to develop an advanced automatic calculation method for the breath-holding index (BHI) to enhance the reliability of cerebrovascular reactivity (CVR) measurements. Material and methods: This study involved the automatic calculation of BHI during the breath-holding maneuver, targeting a reduction in variability and an increase in the accuracy of CVR assessment. Results: The BHI_to_max method was identified as the most effective, which revealed the least variability. This method calculates the steepest slope of blood flow velocity change during CO2-induced vasodilation. By focusing on a minimized time interval and adjusting for potential shifts in the start and end points, this approach captures the most dynamic phase of the cerebrovascular response to CO2 . Conclusions: We propose an automatic calculation method, which accounts for individual differences in CO2 sensitivity and CVR. It offers a potentially more precise and personalized assessment of CVR, leading to a more reproducible and individualized measurement.